A randomized controlled trial of the psychosocial impact of providing internet training and access to older adults - White, H.; McConnell, E.; Clipp, E.; Branch, L. G.; Sloane, R.; Pieper, C.; Box, T. L. (Aging & mental health, 2002)
The Internet (electronic mail and the World Wide Web) may provide new opportunities for communication that can help older adults avoid social isolation. This randomized controlled trial assessed the psychosocial impact of providing Internet access to older adults over a five-month period. One hundred volunteers from four congregate housing sites and two nursing facilities were randomly assigned to receive Internet training or to a wait list control group. The pre & post measures included the UCLA Loneliness scale, modified CES Depression scale, a measure of locus of control, computer attitudes, number of confidants, and overall quality of life. Participants received nine hours of small group training in six sessions over two weeks. Computers were available for continued use over five months and the trainer was available two hours/week for questions. At the end of the trial, 60% of the intervention group continued to use the Internet on a weekly basis. Although there was a trend toward decreased loneliness and depression in intervention subjects compared to controls, there were no statistically significant changes from baseline to the end of trial between groups. Among Internet users ( n = 29) in the intervention group there were trends toward less loneliness, less depression, more positive attitudes toward computers, and more confidants than among intervention recipients who were not regular users ( n = 19) of this technology. Most elderly participants in this trial learned to use the Internet and the majority continued to use it on a weekly basis. The psychosocial impact of Internet use in this sample suggested trends in a positive direction. Further research is needed to determine more precisely, which older adults, residing in which environmental contexts are more likely than others to benefit from this rapidly expanding information and communication link.